Mag deur taal in 1 Johannes - Watt, Jan G. van der (HTS Teologiese Studies / Theological Studies, 2012)
Power through language in 1 John. Power is often exercised through language. Here it is argued that the author of John utilises different language strategies in order to exert power over and to influence his intended readers. His authority lies in his association with the ethos of the group which he feels he represents. From this position he makes his assumptions and builds his arguments. He also makes use of stereotypes to strengthen the identity of his group and to vilify the opponents who are no longer part of the group. His use of terms like koinōnia [fellowship] or filial language is also a powerful way to build the identity and social reality of his group.
free